2003
DOI: 10.1046/j.1537-2995.2003.t01-1-00435.x
|View full text |Cite
|
Sign up to set email alerts
|

The importance of antibodies against low‐incidence RBC antigens in complete and abbreviated cross‐matching

Abstract: Although Ab-LIAs are found coincidentally in the sera of only 2 to 3 percent of patients with other RBC antibodies, they are formed often. Because we found no difference in serologic incompatibility, due to Ab-LIAs, between patients with and without other blood group antibodies, we conclude that blood can be transfused safely to patients without performing a complete cross-match.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 25 publications
(42 reference statements)
3
14
0
1
Order By: Relevance
“…According to Schonewille et al, the prevalence of LIA-Ab varied between 0.3% and 10% and they found no anti-Di a . Anti-Wr a was the most frequent antibody found in this study (14) .…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…According to Schonewille et al, the prevalence of LIA-Ab varied between 0.3% and 10% and they found no anti-Di a . Anti-Wr a was the most frequent antibody found in this study (14) .…”
Section: Discussionsupporting
confidence: 52%
“…These findings differ from those found by Schonewille et al regarding alloimmunization to the Fy a antigen. A prevalence of 1% of anti-Fy a was found while these authors reported 7.3% of anti-Duffy in their study (14) . Twenty patients (8.8%) developed multiple antibodies.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In this issue of TRANSFUSION , Schonewille et al 26 add to the European experience by reviewing data from their hospital from 1978 to 2000; complete crossmatches were performed before 1991. They were particularly interested in abLIA that might appear in patients who had already made other alloantibodies.…”
Section: Incidence Of Antibodies Of Potential Clinical Significancementioning
confidence: 99%
“…However, its corresponding antibody is much more prevalent. The prevalence of anti-Wr a is ranging from 1:56 in healthy blood donors [3] to 5.8% in a range of individuals (blood donors, pregnant women, and hospitalized patients) [4]. Anti-Wr a is capable of causing severe hemolytic transfusion reactions (HTRs) [5] as well as hemolytic disease of the newborn [6], but because of the low frequency of Wr a antigen severe reactions are relatively uncommon.…”
Section: Introductionmentioning
confidence: 99%